IMPLEMENTATION OF ELECTRONIC-BASED GOVERNMENT SYSTEM IN JAKARTA: THE CASE OF CYBER ATTACKS - R. Fauzy; Akbar, Bahrullah; Suwanda, Dadang; Sutiyo; Achmad, Mansyur; Sartika, Ika; Ardiantoro, Juri; Rahmadany , Andi Fitri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Information security in the Electronic-Based Government System (SPBE) of the DKI Jakarta Provincial Government is not yet optimal. The study found that 682 applications are vulnerable to cyber attacks, including the JAKI application in 2023. The causal factors include inadequate security budgets, insufficient personnel with BSSN certification (only 14 out of 31), and infrastructure that does not meet the ISO 27001: 2022 standards. Additionally, Information Security Standard Operating Procedures (SOPs) are not yet available in every Regional Apparatus Organization (OPD), and support from the Regional Council (DPRD) is still minimal. This study aims to analyze the deficiencies in SPBE information security in DKI Jakarta and provide recommendations for improvement. The theoretical foundations used are Government Science, Information Security, and Public Policy Implementation. The research method employs a qualitative approach, using secondary data analysis from official reports and literature reviews on public policy implementation and information security standards. The study concludes that increased budgets, personnel training and certification, as well as infrastructure and SOP improvements are urgently needed. As a global city, Jakarta must improve its information security to protect its data and reputation, thereby enhancing the overall information security index. The recommendations include increasing the information security budget to 6-10% of the total SPBE budget, providing training and certification for all relevant personnel, updating the infrastructure to meet the ISO 27001:2022 standard, and developing and implementing Information Security SOPs in each OPD . Strong policy support from the DPRD is also crucial to strengthen these efforts and support Jakarta's position as a Global City.